2014
DOI: 10.1186/1472-6823-14-96
|View full text |Cite
|
Sign up to set email alerts
|

AMPD1: a novel therapeutic target for reversing insulin resistance

Abstract: BackgroundInsulin resistance is one of the hallmark manifestations of obesity and Type II diabetes and reversal of this pathogenic abnormality is an attractive target for new therapies for Type II diabetes. A recent report that metformin, a drug known to reverse insulin resistance, demonstrated in vitro the metformin can inhibit AMP deaminase (AMPD) activity. Skeletal muscle is one of the primary organs contributing to insulin resistance and that the AMPD1 gene is selectively expressed at high levels in skelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 14 publications
5
12
0
Order By: Relevance
“…Such temporal segregation argues against the dependence of glucose utilization on BCAA catabolism. In addition, genetic disruption of BCAA catabolism ameliorates, rather than exacerbates, insulin resistance in animal models 55, 56 . The elevated BCAA in T2D patients is most likely to be an outcome of nutrient overload, and could contribute to repression of glucose utilization through fuel competition, either directly or via facilitating fat entry or burning in muscle 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Such temporal segregation argues against the dependence of glucose utilization on BCAA catabolism. In addition, genetic disruption of BCAA catabolism ameliorates, rather than exacerbates, insulin resistance in animal models 55, 56 . The elevated BCAA in T2D patients is most likely to be an outcome of nutrient overload, and could contribute to repression of glucose utilization through fuel competition, either directly or via facilitating fat entry or burning in muscle 57 .…”
Section: Discussionmentioning
confidence: 99%
“…A lower incidence of type 2 diabetes in AMPD1 deficient human subjects is also demonstrated [ 6 ]. Therefore, we have studied roles of AMPD1 in the regulation of glucose metabolism using AMPD1 deficient mice made by the gene targeting [ 7 , 8 ]. We demonstrated that AMPD1 deficient mice show augmented glucose tolerance and attenuated insulin resistance under high fat diet feeding triggering insulin resistance [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its deficient expression leads to a less severe state of insulin resistance, improved glucose tolerance and enhanced insulin clearance in mice fed a high fat diet [47]. The activity of AMPD1 purified from skeletal muscle is inhibited by metformin, the most widely used drug for T2D, suggesting a pathogenetic relationship between AMPD1 activity and T2D [48].…”
Section: Pathogenetic Relevance Of Jazf1 Variants To Type 2 Diabetesmentioning
confidence: 99%